2022
DOI: 10.1371/journal.pone.0275579
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in a high income Arab country: A nation-wide cross-sectional survey study

Abstract: Introduction Health literacy is a powerful predictor of health outcomes, but remains a global challenge. There is a paucity of published data and limited understanding of the health literacy of patients in the Middle East. The purpose of this study was to assess the patient health literacy levels in the United Arab Emirates (UAE) and identify associated demographic characteristics. Methods A cross-sectional survey of adult patients attending public and private hospitals and primary care clinics was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…A recent study found that overall adequate HL in the adult UAE population to be approximately 22%. 24 Based on this, the minimum sample size required for this study was estimated to be 610 participants. Previous experience Open access indicated a 25% survey non-response rate, which was compensated.…”
Section: Sampling Methods and Sample Sizementioning
confidence: 99%
“…A recent study found that overall adequate HL in the adult UAE population to be approximately 22%. 24 Based on this, the minimum sample size required for this study was estimated to be 610 participants. Previous experience Open access indicated a 25% survey non-response rate, which was compensated.…”
Section: Sampling Methods and Sample Sizementioning
confidence: 99%
“…A recent study of individuals attending outpatient clinics in the UAE reported that 23.9% of the surveyed population had adequate HL levels [ 20 ]. The sample size calculation for this study was based on an adequate HL prevalence of 0.24, Margin of Error 5% at 95% Confidence level.…”
Section: Methodsmentioning
confidence: 99%
“…The association of the dependent variable (HL level) with the independent variables was conducted using the Chi-Square test. To adjust for confounders, ordinal regression was adopted given that the dependent variable is ordinal (inadequate, marginal, adequate) [ 20 ]. All independent variables that showed statistical significance in Chi-square test were included in the ordinal regression.…”
Section: Methodsmentioning
confidence: 99%
“…Health literacy and medication adherence are strongly associated. Poor glycemic control due to low-health-literacy among diabetes patients reported to both South-East Asian and Middle Eastern countries [45][46][47][48][49][50][51].…”
Section: Patientsmentioning
confidence: 99%